Anti‐tumor effects of miR‐34a by regulating immune cells in the tumor microenvironment - Man Yin; Zhiqiang Zhang; Yunfei Wang (Cancer Medicine, 2023)
Abstract Malignant tumors pose a serious threat to human health. The development of malignant tumors is characterized by uncontrolled cell division and immune evasion. The micro‐ribonucleic acid‐34a (miR‐34a) is a small noncoding single‐stranded ribonucleic acid that is ubiquitously present in normal human tissues. However, it has been confirmed to be dysregulated in a variety of tumor cells. Numerous research have revealed the importance of miR‐34a in the treatment of various malignancies. MiR‐34a deletion can hasten the growth of tumors whereas miR‐34a overexpression suppresses the proliferation, invasion, and migration of cancer cells. Moreover, more recent studies have highlighted its role in immunity and investigated its applicability to particular tumors. Through various immune cells, factors, and other mechanisms, miR‐34a can inhibit tumor carcinogenesis. In view of the important role of miR‐34a in tumors, this research reviewed the aspects of miR‐34a regulation of tumor immune microenvironment to exert anti‐tumor effects in order to clarify the potential immunotherapy value of miR‐34a in tumors.